The role of lysosomes and autophagosomes in frontotemporal lobar degeneration. (19th June 2018) - Bain, H. D. C.; Davidson, Y. S.; Robinson, A. C.; Ryan, S.; Rollinson, S.; Richardson, A.; Jones, M.; Snowden, J. S.; Pickering‐Brown, S.; Mann, D. M. A.
Abstract : Introduction: Cell biological and genetic evidence implicate failures in degrading aggregating proteins, such as tau and TDP‐43, through the autophagy or lysosomal pathways in the pathogenesis of frontotemporal lobar degeneration (FTLD). Methods: We investigated changes in the degradative pathways in 60 patients with different pathological or genetic forms of FTLD employing immunohistochemistry for marker proteins such as lysosomal‐associated membrane proteins 1 (LAMP‐1) and 2 (LAMP‐2), cathepsin D (CTSD) and microtubule‐associated protein 1 light chain 3 alpha (LC3A). Immunostained sections were qualitatively and semi‐quantitatively assessed for the appearance, distribution and intensity of staining in neurones of the dentate gyrus (DG) and CA4 region of the hippocampus, and the temporal cortex (Tcx). Results: Lower levels of neuronal LAMP‐1 immunostaining were present in the DG and Tcx in FTLD‐tau compared to FTLD‐TDP. There was less LAMP‐1 immunostaining in FTLD‐tau with MAPT mutations, and FTLD‐tau with Pick bodies, compared to FTLD‐TDP types A and B, and less LAMP‐1 immunostaining in FTLD‐TDP type C than in FTLD‐TDP types A and B. There was greater LAMP‐1 immunostaining in GRN mutation which may reflect the underlying type A histology rather than mutation. There were no differences in neuronal LAMP‐2, CTSD, EEA‐1 or LC3A immunostaining between any of the five FTLD histological or four genetic groups, nor between FTLD‐TDP and FTLD‐tau. Conclusions: The underlying pathological mechanism in FTLD‐tau may lie with a relative deficiency of lysosomes, or defective vesicular transport, whereas the failure to clear TDP‐43 aggregates may lie with lysosomal dysfunction rather than a lack of available lysosomes or degradative enzymes.